2020
DOI: 10.1128/mra.00851-20
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Traces of Lytic Kaposi Sarcoma-Associated Herpesvirus in Primary Effusion Lymphoma at Single-Cell Resolution

Abstract: Cancer cells of primary effusion lymphoma (PEL) often contain both Kaposi sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV). We measured the interplay of human, KSHV, and EBV transcription in a cell culture model of PEL using single-cell RNA sequencing. The data detect widespread trace expression of lytic KSHV genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…29 To evaluate the transcription profile of KSHV viral genes in KS specimens, Dittmer et al expression in a subpopulation of PEL cell lines by single-cell RNA sequencing. 30,31 Interestingly, BKRF4 (ORF45 homolog of EBV) could be detected in oral hairy leukoplakia 32 and antibodies against BKRF45 were common among Nasopharyngeal carcinoma patients. 33 The expressions of ORF45 in KS lesion and PEL cell imply possible roles of ORF45 in KSHV pathogenesis.…”
Section: Transcription and Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 To evaluate the transcription profile of KSHV viral genes in KS specimens, Dittmer et al expression in a subpopulation of PEL cell lines by single-cell RNA sequencing. 30,31 Interestingly, BKRF4 (ORF45 homolog of EBV) could be detected in oral hairy leukoplakia 32 and antibodies against BKRF45 were common among Nasopharyngeal carcinoma patients. 33 The expressions of ORF45 in KS lesion and PEL cell imply possible roles of ORF45 in KSHV pathogenesis.…”
Section: Transcription and Expressionmentioning
confidence: 99%
“…To evaluate the transcription profile of KSHV viral genes in KS specimens, Dittmer et al 13 performed real‐time PCR array analysis and found that ORF45 transcript can be detected in 8 out of 21 KS specimens; Hosseinipour et al 14 used improved quantitative RT‐PCR array and found ORF45 transcript is detectable in 27 out of 35 KS lesions; and Tso et al detected ORF45 expression in 3 out of 4 KS lesions by RNA‐seq 15 . In PEL cells, Rondeau et al and Landis et al detected ORF45 expression in a subpopulation of PEL cell lines by single‐cell RNA sequencing 30,31 . Interestingly, BKRF4 (ORF45 homolog of EBV) could be detected in oral hairy leukoplakia 32 and antibodies against BKRF45 were common among Nasopharyngeal carcinoma patients 33 .…”
Section: Transcription and Expressionmentioning
confidence: 99%
“…A pipeline optimized for simultaneously measuring viral and human transcripts ( 12 , 13 ) was modified for the analysis of EBV and HHV-6. Cell Ranger (10X Genomics) was used to demultiplex raw base call files, trim template switching oligo and poly(A) sequences, align reads, and count unique molecular identifiers (UMIs).…”
Section: Announcementmentioning
confidence: 99%
“…Sequencing of the lymphoma cell line BCP-1 showed high expression of a subset of lytic genes, including PAN and a cluster of genes involved in immune regulation (K2, K4, K5) [ 39 ]. Single-cell RNA sequencing of the BC1 PEL line also detected many lytic genes in up to 50% of the cells, but at very low levels per cell [ 40 ].…”
Section: What Is the Contribution Of Lytic Replication To Tumorigenesis?mentioning
confidence: 99%